Pendampingan Spiritual dalam Asuhan Keperawatan Sebagai Upaya Penyembuhan Pasien - Sinanto, Rendi; Nadur, Eduardus; Axmalia, Astry (Infomasi dan Promosi Kesehatan, 2023)
Nursing care is a series of interactions between nurses and patients with the aim of achieving the patient's independence in caring for himself, nursing care that is given holistically including biological, psychological, sociological, and spiritual aspects. This study aims to see what factors influence spiritual accompaniment in nursing care. The method used in this research is a literature review by taking data sources through garuda.ristekbrin.go.id which was published in the 2015-2021 period, can be downloaded on March 2-4, 2021. After selecting and identifying according to inclusion criteria, there are 13 article reviewed. The results showed that the factors that influence spiritual assistance in nursing care as a patient's healing are knowledge, perceptions, and good attitudes about spiritual health in addition to motivation, family support, and self-efficacy of nurses in fulfilling spiritual needs. Then the factor of a nurse's length of work also becomes a supporter of spiritual assistance. Spiritual health is very effective in supporting the healing process for patients. Suggestions for nurses to increase knowledge and attitudes about the spiritual needs of patients, so as to produce good nursing care.